2019
DOI: 10.1155/2019/4246780
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Bacterial Urinary Tract Infections and Associated Factors among Patients Attending Hospitals in Bushenyi District, Uganda

Abstract: Urinary tract infections (UTIs) are one of the major causes of morbidity and comorbidities in patients with underlying conditions, and it accounts for the majority of the reasons for hospital visit globally. Sound knowledge of factors associated with UTI may allow timely intervention that can easily bring the disease under control. This study was designed to determine the prevalence of UTI by isolating and characterizing the different bacterial etiological agents and to evaluate the factors associated with UTI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

47
144
11
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(206 citation statements)
references
References 39 publications
(46 reference statements)
47
144
11
4
Order By: Relevance
“…Overall prevalence of UTI in this study was found to be 13.5% with higher prevalence among females (23.1%) than in the males (6.2%). The prevalence of UTIs in the current study is similar to the finding by Pradhan et al 13 but is lower than the studies by Mwaka et al (10%), 14 Tibyangye et al (22%) 15 and Odoki et al (32%) 16 from Uganda; and Khatiwada et al from Nepal. 17 The possible explanation for the variation in the prevalence in these studies could be the differences in the types of the populations studied.…”
Section: Discussionsupporting
confidence: 87%
“…Overall prevalence of UTI in this study was found to be 13.5% with higher prevalence among females (23.1%) than in the males (6.2%). The prevalence of UTIs in the current study is similar to the finding by Pradhan et al 13 but is lower than the studies by Mwaka et al (10%), 14 Tibyangye et al (22%) 15 and Odoki et al (32%) 16 from Uganda; and Khatiwada et al from Nepal. 17 The possible explanation for the variation in the prevalence in these studies could be the differences in the types of the populations studied.…”
Section: Discussionsupporting
confidence: 87%
“…This present study also implicated Ipogun-Ayo to have the highest prevalence of (28.72%). The presence of these organisms in urine samples was however, substantial to the findings of [21,22]. Staphylococcus aureus to be the most frequently occurred uropathogen with 27.2%.…”
Section: Difference Between Means Was Determined Bysupporting
confidence: 51%
“…is common to cause urinary tract infections in younger persons. Odoki et al, [21] also recorded S. aureus to be more prominent to cause UTIs among pregnant women in Uganda.…”
Section: Difference Between Means Was Determined Bymentioning
confidence: 97%
“…These findings concur with those in similar studies carried out in Europe and Asia. The predominance of Enterobacteriaceae could be due to their omnipresence in the environment (18,19). Furthermore, Escherichia coli is the most predominant normal aerobic intestinal flora with various strains of specific virulence factors that interact with the host to overcome host defenses in the urinary tract and to stimulate an infection.…”
Section: Discussionmentioning
confidence: 99%